2007
DOI: 10.1007/s00240-007-0102-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate synthesis from hydroxypyruvate in vitamin-B6-deficient rats

Abstract: We studied the effects of an intravenous hydroxypyruvate load on endogenous oxalogenesis in rats receiving a standard diet or a vitamin-B6-deficient diet. Twelve male Wistar rats were randomized to two groups and were fed either a standard diet or a vitamin-B6-deficient diet for 3 weeks. Then the animals received an intravenous infusion of 100 mg/ml (960.6 micromol/ml) of hydroxypyruvate slowly over 10 min. Urine samples were collected just before hydroxypyruvate infusion and at hourly intervals until 5 h afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 20 publications
4
10
1
Order By: Relevance
“…The overall study protocol has been reported elsewhere 7,8 . Briefly, 24 male Wistar rats weighing 188.65 ± 6.10 g (mean ± SD) were randomly divided into two groups (an ethylene glycol group and a glycine group) of 12 animals each.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall study protocol has been reported elsewhere 7,8 . Briefly, 24 male Wistar rats weighing 188.65 ± 6.10 g (mean ± SD) were randomly divided into two groups (an ethylene glycol group and a glycine group) of 12 animals each.…”
Section: Methodsmentioning
confidence: 99%
“…The method of sample collection has been explained elsewhere 7,8 . In short, hourly urine samples were collected by bladder puncture at 0 h and every hour subsequently until 5 h after infusion of ethylene glycol or glycine.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, pyridoxine can act as a cofactor for various enzymes in the tricarboxylic acid cycle as well, leading to a decreased synthesis of citrate. Thus, under the condition of pyridoxine deficiency, citrate metabolism may be impaired, leading to a lower urinary citrate concentration and increased risk of precipitation with CaOx (103) . To the authors' knowledge, the effect of pyridoxine on urinary citrate excretion in cats has not been studied.…”
Section: Urinary Oxalatementioning
confidence: 99%